Bacteriologically confirmed pulmonary tuberculosis patients: Loss to follow-up, death and delay before treatment initiation in Bulawayo, Zimbabwe from 2012–2016. (November 2018) - Mugauri, Hamufare; Shewade, Hemant Deepak; Dlodlo, Riitta A.; Hove, Sithokozile; Sibanda, Edwin
Highlights: One in five people with drug-susceptible, bacteriologically confirmed tuberculosis was not initiated on treatment which constituted pre-treatment loss to follow-up (LTFU). Pre-treatment deaths accounted for approximately half of all pre-treatment LTFU cases in a city with high HIV prevalence (18.7%). There were long delays between sputum receipt to testing, and diagnosis to treatment initiation, though the delay was on a descending trajectory between 2012 and 2016. Old age, male or missing gender, and being HIV-positive or having an unknown HIV status increased the risk of pre-treatment LTFU significantly. Abstract: Objective: To quantify and assess trends and risk factors for loss to follow-up (LTFU) and delays before treatment initiation among bacteriologically confirmed pulmonary tuberculosis (TB) patients (laboratory-diagnosed) in Bulawayo, 2012–16. Design: Cohort study using secondary programme data. Presumptive TB patients' sputum samples were sent to the laboratory from the 19 primary health care clinics. Laboratory-diagnosed patients (microscopy or Xpert MTB/RIF) were tracked for treatment registration at the clinics. Results: Of 2443 laboratory-diagnosed patients, the mean (standard deviation, SD) delay from sputum receipt at the laboratory to testing was 2.7(1.6) days and from testing to result dispatch was 8.8(5.8) days. A total of 508(20.8%) were LTFU which included 252(10.3%) deaths. While the number of laboratory-diagnosed patients reduced over years, there was a significant increase in pre-treatment LTFU and death. Independent predictors of pre-treatment LTFU were age above 65 years, male gender and HIV positive/unknown. In addition, delay (≥3 days) between sputum receipt and testing was significantly associated with pre-treatment death. Among registered patients (n = 1935), the mean (SD) delay to initiate treatment was 29.1 (21.6) days which significantly declined over the years. Patients registered as new TB had significantly long treatment delay. Conclusions: Interventions to mitigate the risk factors for high loss to follow-up, deaths and delays before TB treatment are urgently required.